Osteoarthritis and Falls: Is there a Link? - Ray Marks (Journal of Aging Research And Healthcare, 2020)
Osteoarthritis, a widespread joint disease, commonly results in considerable pain and functional disability, especially among older adults. At the same time, falls and fall injuries, also common among the older population, may not only contribute to the onset of osteoarthritis, but once established, to falls that lead to fractures and disability in their own right. But what does the research show specifically? Objective This report aimed to examine what is known about the interrelationship between falls and osteoarthritis and the implications that can be drawn from this information. Methods Using the PUBMED data base, studies describing an association between osteoarthritis and falls were sought. Those fulfilling the eligibility criteria were reviewed and summarized in narrative form. Results Consistent support for an osteoarthritis-falls associated linkage is limited and not as robust as one would predict. Whether the observed associations between these health determinants are a cause of osteoarthritis, a consequence or both, or simply spurious findings is hard to decipher. Conclusion More numerous and carefully designed research to examine this issue is warranted and may be extremely helpful in preventing, as well as ameliorating a high degree of excess disability and associated fiscal costs due to both falls as well as osteoarthritis among the elderly.
Keywords: Osteoarthritis